Peningkatan Hasil Belajar Perubahan Sifat Benda Melalui Model Kontekstual Yang Dilengkapi Media Realia Di SDN Wonoketingal 1 Demak - Sulikhah Sulikhah (Universitas Muria Kudus, 2018)
The purpose of this study include: 1) to describe the learning outcomes of science Class V students in SD Negeri Wonoketingal 1 District Karanganyar Demak Regency material changes the nature of the object. 2) to improve teachers' knowledge of appropriate and targeted teaching methods and to increase teaching motivation. 3) to improve students' motivation in following science lesson, especially on basic competence of change of object properties at SD Negeri Wonoketingal 1 District Karanganyar Demak Regency. This study uses a classroom action research design with direct planning, action, observation and reflection. Based on observation h and the results of research conducted at SDN Wonoketingal 1, it is known that the implementation of science learning in class V as a whole has been running. However, in the Competence of Change of Nature Nature, there are still many students who have not maximized their learning outcomes, such as the students only answer some teacher questions therefore the teacher uses contextual learning model with the aid of realia media seen there is an increase of the average value of 63,33 in cycle 1, increased to an average of 80.00 in cycle 2, it means already above KKM 70.00. The increase is in addition to the learning model conducted by contextual teachers so that learners in understanding the subject matter associated with the context of everyday life through the media realia learning more meaningful. Students are active because they use various sources, more integrated learning students feel happy not bored, sharing with friends, critical students and creative teachers.Thus there is an increase of 16.67 because with contextual learning through media realia students more active, disciplined and confident.